Assistance for Adiwiyata school teachers in learning innovation with an integrated STEAM-H approach - Fatimah, Ai Tusi; Rahayu, Febriani; Suparman, Chandra; Insani, Ismatal Qisthi (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
Learning innovations to support environmentally friendly behavior in Adiwiyata schools at the technical level are still complained of as difficult for teachers to implement. Integrated STEAM-H (science, technology, engineering, agriculture, mathematics, and health) is a learning approach that can be used by teachers to create innovative learning across subjects. This community service activity was carried out to assist sixth-grade Madrasah Ibtidaiyah Handapherang (equivalent to elementary school) teachers in designing, implementing, and assessing learning using an integrated STEAM-H approach. This mentoring method is carried out through the stages of preparation, implementation, and evaluation. The preparatory stage is carried out through focus group discussions to build learning tools and prepare tools and materials as learning media. The implementation stage is the implementation of the planning stage. Evaluation stage of the entire series of activities. Assistance produces teaching modules across subjects, namely mathematics, and science, building hydroponic project-based learning, providing meaningful learning for students that integrates agriculture, science, mathematics, technology, engineering, and health in a hydroponic vegetable cultivation project. The results of this assistance become a reference for innovative learning at the Madrasah Ibtidaiyah Handapherang to be further developed to support environmentally friendly behavior at Adiwiyata schools.